2019
DOI: 10.1021/acs.est.9b01243
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Photolysis of Safener Benoxacor and Herbicide Metolachlor as Mixtures on Simulated Soil Surfaces

Abstract: Benoxacor is a safener paired with the high-use herbicide S-metolachlor. Commercial formulations containing both compounds are sprayed onto soil pre-emergence to enhance yields of corn. In this study, we evaluated the sunlight photolysis of metolachlor and benoxacor, individually and as mixtures, in three different reaction environments: in water and on two soil-simulating surfaces (quartz and kaolinite). When irradiated individually, benoxacor degraded at least 19 times faster than metolachlor in each reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Importantly, dichloroacetamide safeners can undergo photolysis (Kral et al, 2019;Su et al, 2019), hydrolysis (McFadden et al, 2022), abiotic reductive dechlorination (Ricko et al, 2020;Sivey & Roberts, 2012;Xu et al, 2020Xu et al, , 2022, and *Indicates significant difference compared with controls (shown as 0 for each figure). AD, AD-67.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, dichloroacetamide safeners can undergo photolysis (Kral et al, 2019;Su et al, 2019), hydrolysis (McFadden et al, 2022), abiotic reductive dechlorination (Ricko et al, 2020;Sivey & Roberts, 2012;Xu et al, 2020Xu et al, , 2022, and *Indicates significant difference compared with controls (shown as 0 for each figure). AD, AD-67.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, dichloroacetamide safeners can undergo photolysis (Kral et al, 2019; Su et al, 2019), hydrolysis (McFadden et al, 2022), abiotic reductive dechlorination (Ricko et al, 2020; Sivey & Roberts, 2012; Xu et al, 2020, 2022), and biotransformation (Abu‐Qare & Duncan, 2002) in the environment. These processes can result in the safener changing into structures like those of herbicides, which could be more toxic than the parent (Abu‐Qare & Duncan, 2002; Sivey & Roberts, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the additive (co-formulation compound) benoxacor, which is used as a safener (i.e. a compound used in combination with herbicides to reduce negative effects on crops) of the herbicide metolachlor, accelerates the photodegradation of the active ingredient on soil surfaces, lessening its toxicity [ 341 ]. The extent to which biocides are photodegraded is also highly dependent on where the biocide residues occur.…”
Section: Effects On Agriculture and Food Productionmentioning
confidence: 99%
“… 2 6 Given their widespread use (estimated >8 × 10 6 kg/year globally) and occurrence in the environment, there is a growing body of research regarding the environmental fate and effects of dichloroacetamides. 2 , 4 10 Recent studies have demonstrated moderate acute toxicity of dichloroacetamides toward model freshwater fish species (LC 50 values of 1.4–4.6 mg/L), 11 , 12 and toxicity screening data available from the U.S. Environmental Protection Agency (EPA) indicate the potential for benoxacor to interact with multiple human nuclear receptors. 13 The EPA has also identified AD-67 and furilazole as “likely to be carcinogenic to humans”.…”
Section: Introductionmentioning
confidence: 99%
“…The dichloroacetamide safeners AD-67, benoxacor, dichlormid, and furilazole are commonly included in chloroacetamide herbicide formulations to selectively protect crops against herbicide toxicity. , Dichloroacetamides (Figure ) are modestly hydrophilic (log K ow 1.84–3.19) and mobile in aqueous environments, which has led to their detection in Midwestern drinking water sources at concentrations of up to 190 ng/L. Given their widespread use (estimated >8 × 10 6 kg/year globally) and occurrence in the environment, there is a growing body of research regarding the environmental fate and effects of dichloroacetamides. , Recent studies have demonstrated moderate acute toxicity of dichloroacetamides toward model freshwater fish species (LC 50 values of 1.4–4.6 mg/L), , and toxicity screening data available from the U.S. Environmental Protection Agency (EPA) indicate the potential for benoxacor to interact with multiple human nuclear receptors . The EPA has also identified AD-67 and furilazole as “likely to be carcinogenic to humans”. , Furthermore, some dichloroacetamide safeners, including dichlormid and benoxacor, can transform under environmentally relevant conditions to yield products with increased biological activity that may pose even greater risks to the environment and human health.…”
Section: Introductionmentioning
confidence: 99%